Overview of Various Models of Insulators with Thin Coating Layers - Dhahbi-Megriche Nabila; Nouir-Masmoudi Haifa; Kaddeche Slim (EPJ Web of Conferences, 2025)
In this study, the electric potential distribution along an insulator model coated with a thin stress grading material was analyzed using a numerical formulation based on the Spectral Collocation Method (CSM). Comparative assessments against analytical solutions, established numerical approaches from the literature, and the Finite Difference Method (FDM) validated the accuracy and robustness of the proposed method. The CSM demonstrated numerical precision equivalent to that of FDM while offering significant advantages in terms of computational efficiency and implementation simplicity when compared to both FDM and the Finite Element Method (FEM). Moreover, the evaluation of the maximum electric field reduction at the high-voltage electrode quantitatively highlighted the effectiveness of incorporating nonlinear conductivity within the grading layer.